SOCIAL REPRESENTATION OF ACADEMIC UNDERACHIEVEMENT AMONG PRIMARY SCHOOL STUDENTS: A TEACHERS’ PERSPECTIVE - TUFEANU Magda; ROBU Viorel (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
Successful school adjustment is a key factor for the developmental trajectory of children and adolescents. Today’s global society is characterized by rapid economic, social and cultural changes. Therefore, academic underachievement is a risk factor that can negatively impact the transition from childhood to adulthood. This study examines the social representation that teachers have of academic underachievement among primary school students. The participants (N = 81; average length of service = 15.4 years) completed a standardized task based on the free association technique. The universe of associations was structured using lexical-semantic analysis, as well as prototypical analysis. The results indicate a clustering of associations along two dimensions regarding the causes and consequences of academic underachievement. The findings are analyzed with reference to practical measures that can be adopted to prevent and reduce academic underachievement.